2020
DOI: 10.1016/j.ijrobp.2020.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Prophylactic Cranial Irradiation With Hippocampal Avoidance on Neurocognitive Function in Patients With Limited Disease Small Cell Lung Cancer. A Multicenter Phase 2 Trial (SAKK 15/12)

Abstract: Purpose: Our purpose was to evaluate neurocognitive function (NCF) and clinical outcomes after early hippocampal avoidance (HA) prophylactic cranial irradiation (PCI) in limited disease (LD) small cell lung cancer (SCLC). Methods and Materials: In a phase 2 trial, patients with LD SCLC received HA-PCI concomitant with the second cycle of chemotherapy and thoracic radiation therapy. All patients underwent objective NCF testing at baseline, 6 weeks, and 6 and 12NotedAn online CME test for this article can be tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…PCI is identified as one of the major treatments for SCLC [ 6 ]; however, its preventive effect is not optimal due to high recurrence rate and neurotoxicity [ 5 , 23 25 ]. Several clinical studies have believed that hippocampus-sparing radiation avoids the neurotoxic side effects to some extent [ 8 , 26 28 ]. NRG CC001, a phase 3 trial based on the RTOG0933 study, showed that HA-WBRT plus memantine better preserves cognitive function and patient-reported symptoms, with no difference in intracranial PFS and OS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCI is identified as one of the major treatments for SCLC [ 6 ]; however, its preventive effect is not optimal due to high recurrence rate and neurotoxicity [ 5 , 23 25 ]. Several clinical studies have believed that hippocampus-sparing radiation avoids the neurotoxic side effects to some extent [ 8 , 26 28 ]. NRG CC001, a phase 3 trial based on the RTOG0933 study, showed that HA-WBRT plus memantine better preserves cognitive function and patient-reported symptoms, with no difference in intracranial PFS and OS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For SCLC patients, the incidence of BM in hippocampal is generally about 5% both at diagnosis and after PCI, 26,27 indicating that it may be feasible to decrease the BM rate and to reduce the neurocognitive toxicities by PCI with hippocampal avoidance. 28,29 A multicentre randomized phase 3 trial (NCT01780675) investigated memory functioning and safety after PCI with or without hippocampus sparing in SCLC using the Hopkins Verbal Learning Test-Revised (HVLT-R). The results showed that PCI with hippocampal sparing did not affect the decline of neurocognitive function and increased brain metastasis compared to standard PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Our current study adds to the emerging body of evidence on HA-PCI from RT0G 0933 [5] and, more recently, from Redmond et al [13], OC-0503 [14], and SAKK 15/12 (15). RTOG 0933 [5] randomised 110 patients who already had brain metastases at least 5mm beyond the hippocampi to whole brain radiotherapy or hippocampal-avoidance whole brain radiotherapy.…”
Section: Discussionmentioning
confidence: 88%
“… In the SAKK 15/12 trial the expansion from the hippocampi to the hippocampal avoidance zones was 2 mm, where specified all other trials used a 5mm expansion [ 15 ]. CTC — clinical target volume; HAZ — hippocampal avoidance zone; PTV — planning target volume …”
Section: Figurementioning
confidence: 99%